Media Benda Nyata Untuk Penyelesaian Soal Cerita Matematika Siswa Diskalkulia - Madechan, ; Brillante Nena Desiana, (Pendidikan Luar Biasa, 2008)
Research by using real object media aimes to prove its influence to the increase of ability in finishing question story form of math to the dyscalculia students. In this research used real object media since this learning media could stimulate and motivate student in learning activity that student can easily absorb learning materials. Analyzing data by using technigue the sign test, it shown result Z counting = 2,68 and Z table = 1,64. It means 2,68 > 1,64 so, Ho denied and Ha accepted that can be concluded that there is an influence of using real object media in increasing ability of finishing question story form of math to the dyscalculia studened in SDN Kedungsumber Balongpanggang Gresik. The conclusion of this research is that there is improvement of ability in finishing question story form of math by the second year class  dyscalculia student  (40 %) by using real object media in SDN Kedungsumber Balongpanggang Gresik, showing form the increasing result of students tests before using real object media (28%) and after using real object media (68%).